Origin of the Quaternary Deposits of Nepal and their Neotectonic Significance - Sharma, Toran (Himalayan Review, 2011)
Not available. Key words: Quaternary Deposits; Neotectonic Significance; Earth's crust; Nepal The Himalayan Review Vol. 12, 1980 Page: 31-43 Uploaded Date: April 5, 2011